Evaluasi Dampak Sosial dan Ekonomi Pengembangan Kawasan Industri Wilmar Serang - Ginanti Fajar; Ipah Ema Jumiati; Delly Maulana (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
The development of the Wilmar Serang industrial area is a government effort to increase economic growth and people's welfare. In practice, the policy has an impact on society. The impacts generated in this study are limited to economic impacts and social impacts. The purpose of this research is to identify the factors that influence the impact, identify forms of government intervention in reducing the impact, and evaluate the impact. The method used is descriptive qualitative method and determination of research informants using purposive sampling. The research location was carried out in Kramatwatu District, Serang Regency. Data collection techniques were carried out through interviews and documentation studies. Test the validity of the data using the triangulation technique which is carried out continuously until there is no need to confirm the informant. The results of this study show what are the factors that influence the impact, the form of government intervention in reducing the impact as well as the results of policy evaluation based on 6 (six) evaluation criteria which show that the Wilmar Serang industrial area development policy has not been implemented properly in its entirety.